2020
DOI: 10.3389/fpsyg.2020.01926
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Career Adaptability, the Tendency to Consider Systemic Challenges to Attain a Sustainable Development, and Hope to Improve Investments in Higher Education

Abstract: Based on the life design paradigm and career construction adaptation model and on recent directions from the perspective of sustainable and inclusive career guidance, the study aimed at examining the relationship between career adaptability, the tendency to consider systemic challenges to attain sustainable development, and state personal and social hope and their role on the tendency to invest in higher education. The analyses carried out involving 416 Italian high school students found that career adaptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Career adaptability is an important factor for an individual to effectively cope with career uncertainty and job role ambiguity, and it refers to the individual's coping ability when dealing with the changes of current and expected tasks and career roles [13,24]. Career adaptability plays an important role in realizing sustainable development [25]. Cultivating career adaptability can promote the transition from school to work, thus improving the chances for individuals to nd high-quality jobs and helping individuals to transform from university to work [26,27].…”
Section: Career Adaptabilitymentioning
confidence: 99%
“…Career adaptability is an important factor for an individual to effectively cope with career uncertainty and job role ambiguity, and it refers to the individual's coping ability when dealing with the changes of current and expected tasks and career roles [13,24]. Career adaptability plays an important role in realizing sustainable development [25]. Cultivating career adaptability can promote the transition from school to work, thus improving the chances for individuals to nd high-quality jobs and helping individuals to transform from university to work [26,27].…”
Section: Career Adaptabilitymentioning
confidence: 99%
“…Moreover, the presence of multiple inequalities has had significant impacts on the well-being of individuals, groups, and communities. Issues such as poverty, social barriers, significant competitiveness and precariousness are constantly being experienced (Di Maggio et al, 2020). The Covid-19 pandemic has contributed to accentuate these dimensions of mutability, nonlinearity and instability, even more increasing the sense of uncertainty, anomie and apprehension (Dryhurst et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the life design approach emphasized that promoting the tendency to understand and manage a complex system is the only option to design the future and address challenges. It supports people to handle global warming, economic and opportunity disparities in the world, discrimination, and environmental degradation [1,2,5]. Taking this into consideration, different authors suggest focusing attention on cosmopolitanism [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The person is not designed by the context but is in interdependence with it. Recently, based on the life design approach and considering the new global challenges that characterize today's world and societies, several scholars have suggested that career guidance should promote abilities, competencies, and attitudes that can help adolescents to consider global challenges in their career planning to move towards an inclusive and sustainable global development [5,27]. In this perspective, it may be important to involve cosmopolitanism in the future life design process because it could help adolescents move towards a more satisfactory personal and professional future that is also more oriented towards creating an inclusive and sustainable future society [3,[6][7][8][19][20][21].…”
Section: Introductionmentioning
confidence: 99%